Formation of ordered array of core/shell ZnS/Ge/ZnS nanostructures by thermal evaporation method. Issue 9 (2nd May 2014) - Beltiukov, A.; Valeev, R.; Romanov, E.; Mukhgalin, V.
Abstract This paper reports the results of studies of ZnS/Ge/ZnS nanostructures, obtained by high vacuum thermal deposition of ZnS and Ge powders into porous anodic aluminium oxide (AAO) with different diameters of pores. Scanning electron microscopy (SEM) investigations reveal two types of nanostructures having the form of rings (sample with diameter of pores 70 nm) and rods (samples with diameter of pores 80 and 110 nm). It is also shown that the other porosity parameters such as interporous distances affect the formation of a particular type of nanostructures. X‐ray and electron diffraction study show two phases, ZnS and Ge. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)